Optimal Path Algorithm Analysis of GPS Navigation Based on A Algorithm - Ding, Ming Li (Applied Mechanics and Materials, 2014)
The optimal path algorithm analysis of GPS navigation in taxi management system based on A* algorithm was introduced in this paper. Through improving the traditional Dijkstra algorithm and avoiding problems such as time-consuming and low efficiency in Dijkstra algorithm with traversal search for each node, A* algorithm could help the taxi find the optimal path and bring convenience for traffic management.